2019
DOI: 10.1108/hff-11-2017-0465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thickness and thermal conductivity of metal foams filled in a vertical channel – a numerical study

Abstract: Purpose This paper aims to discuss about the two-dimensional numerical simulations of fluid flow and heat transfer through high thermal conductivity metal foams filled in a vertical channel using the commercial software ANSYS FLUENT. Design/methodology/approach The Darcy Extended Forchheirmer model is considered for the metal foam region to evaluate the flow characteristics and the local thermal non-equilibrium heat transfer model is considered for the heat transfer analysis; thus the resulting problem becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The assumptions made in the present numerical examination are as follows: The flow is steady and incompressible. The gravitational impact on the fluid flow is assumed to be negligible (Huang et al , 2010). The experimental and numerical investigation (Calmidi and Mahajan, 2000) shows the insignificant effect of thermal dispersion in foam-air combination because of high heat conducting capacity of metal foams, hence thermal dispersion is neglected in the presented study. In the investigations (Garrity et al , 2010; Baragh et al , 2018; Boules et al , 2021), the influence of thermal radiation was found to be negligible, hence the same condition is adopted in the current study. The flow mixing due to the tortuous path of the metal foam is not considered (Kotresha and Gnanasekaran, 2018a). Metal foam region is assumed as isotropic homogeneous porous media (Kotresha et al , 2019; Kotresha and Gnanasekaran, 2018b; Garrity et al , 2010).…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…The assumptions made in the present numerical examination are as follows: The flow is steady and incompressible. The gravitational impact on the fluid flow is assumed to be negligible (Huang et al , 2010). The experimental and numerical investigation (Calmidi and Mahajan, 2000) shows the insignificant effect of thermal dispersion in foam-air combination because of high heat conducting capacity of metal foams, hence thermal dispersion is neglected in the presented study. In the investigations (Garrity et al , 2010; Baragh et al , 2018; Boules et al , 2021), the influence of thermal radiation was found to be negligible, hence the same condition is adopted in the current study. The flow mixing due to the tortuous path of the metal foam is not considered (Kotresha and Gnanasekaran, 2018a). Metal foam region is assumed as isotropic homogeneous porous media (Kotresha et al , 2019; Kotresha and Gnanasekaran, 2018b; Garrity et al , 2010).…”
Section: Methodsmentioning
confidence: 93%
“…The flow mixing due to the tortuous path of the metal foam is not considered (Kotresha and Gnanasekaran, 2018a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is crucial to analyze the thermo-hydraulic behavior of metal foams with both flow resistance and heat transfer enhancement. Several factors that influence flow and heat transfer through metal foam include material aspects (thermal conductivity [11]), structural aspects (porosity and pore density [12]), configurational aspects (thickness [11,13] and partial filling [14,15]), the foam geometrical aspect (shape [16]), and the arrangement aspect (foam multi-layer [17]), etc. It is interesting to note that different combinations of these aspects result in varied pressure drop and heat transfer, thus allowing a better trade-off between enhanced heat transfer with the accompanied increased pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of the numerical modeling, finding an adequate representation of clusters of obstacles that captures the relevant features of the flow effectual for design purposes at reasonable computational cost is not a trivial task (Kotresha and Gnanasekaran, 2019). Homogenization is an elegant and efficient method in pursuing this goal (Jumah et al, 2001;Blanco et al, 2017;Hayat et al, 2018).…”
Section: Introductionmentioning
confidence: 99%